(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper; dispersion compensating fibers are used to compensate for the positive dispersion accumulated over the length of fiber. Post dispersion compensation scheme is employed for dispersion compensation. NRZ modulation format is employed. The performance of this scheme is analyzed and then the optimization of this scheme is done by different wavelengths of C band. The investigation is done on detailed simulative analysis using optisystem.